Magnetic‐Field Tunable Intertwined Checkerboard Charge Order and Nematicity in the Surface Layer of Sr2RuO4. Issue 32 (27th June 2021) - Marques, Carolina A.; Rhodes, Luke C.; Fittipaldi, Rosalba; Granata, Veronica; Yim, Chi Ming; Buzio, Renato; Gerbi, Andrea; Vecchione, Antonio; Rost, Andreas W.; Wahl, Peter
Abstract: In strongly correlated electron materials, the electronic, spin, and charge degrees of freedom are closely intertwined. This often leads to the stabilization of emergent orders that are highly sensitive to external physical stimuli promising opportunities for technological applications. In perovskite ruthenates, this sensitivity manifests in dramatic changes of the physical properties with subtle structural details of the RuO6 octahedra, stabilizing enigmatic correlated ground states, from a hotly debated superconducting state via electronic nematicity and metamagnetic quantum criticality to ferromagnetism. Here, it is demonstrated that the rotation of the RuO6 octahedra in the surface layer of Sr2 RuO4 generates new emergent orders not observed in the bulk material. Through atomic‐scale spectroscopic characterization of the low‐energy electronic states, four van Hove singularities are identified in the vicinity of the Fermi energy. The singularities can be directly linked to intertwined nematic and checkerboard charge order. Tuning of one of these van Hove singularities by magnetic field is demonstrated, suggesting that the surface layer undergoes a Lifshitz transition at a magnetic field of ≈32T. The results establish the surface layer of Sr2 RuO4 as an exciting 2D correlated electron system and highlight the opportunities for engineering the low‐energy electronic states in these systems. Abstract : Using ultralow temperature scanning tunneling microscopy and spectroscopy, the low‐energy electronic structure of the surface layer of Sr2 RuO4 is revealed. Small structural distortions lead to radically different properties compared to the bulk with multiple van Hove singularities close to the Fermi energy giving rise to nematic and charge orders. The van Hove singularities can be manipulated by a magnetic field.